Satu daripada Tiga Belas: Sabah dan Sarawak dalam Pembentukan Malaysia, 1961-1963 - Bilcher Bala (2018)
The formation of Malaysia is a process of merging an independent state with British 'self-governing' colonies in Southeast Asia to form a new federal state. The merger was legally compromised involving three levels of comprehensive consultation from 1961 to 1963, namely the MSCC, the Cobbold Commission, and the IGC. There has been confusion among Malaysians on the meaning and history of Malaysia Day, which was celebrated on 16 September. Sabah and Sarawak are the 12th and 13th states in the Federation of Malaysia. Since 2010, the people of Sabah and Sarawak have begun to polemics about two historical dates, namely August 31 and September 16 which directly disputes the status quo of 'state' within the Federation of Malaysia. This article attempts to provide a historical perspective based on the major sources during the process.